2021
DOI: 10.1080/19476337.2021.1914176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bile salt hydrolase-activeLactobacillus plantarumY15 on high cholesterol diet induced hypercholesterolemic mice

Abstract: This study aimed to elucidate the underlying mechanisms for the protective effect of Lactobacillus on hypercholesterolemia. Firstly, twenty Lactobacillus strains were screened for potential probiotics with high bile salt hydrolase (BSH) activity using in vitro methods. Secondly, hypercholesterolemic mice induced by a cholesterol-enriched diet were administrated by the probiotic candidate strain L. plantarum Y15, identified from the screen. Results in vitro showed that L. plantarum Y15 possessed high BSH activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Moreover, Lachnoclostridium and Desulfovibrio might be responsible for an increase in TC and LDL-C, respectively, in the serum and liver. Desulfovibrio and Lachnoclostridium were significantly more abundant in the MC group and decreased after the supplementation of L. plantarum Y15 [36], indicating that L. plantarum WLPL21 alleviated hypercholesterolemia by increasing the abundance of Allobaculum, Blautia, and Lactobacillus and reducing that of Lachnoclostridium and Desulfovibrio.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, Lachnoclostridium and Desulfovibrio might be responsible for an increase in TC and LDL-C, respectively, in the serum and liver. Desulfovibrio and Lachnoclostridium were significantly more abundant in the MC group and decreased after the supplementation of L. plantarum Y15 [36], indicating that L. plantarum WLPL21 alleviated hypercholesterolemia by increasing the abundance of Allobaculum, Blautia, and Lactobacillus and reducing that of Lachnoclostridium and Desulfovibrio.…”
Section: Discussionmentioning
confidence: 93%
“…Activated cultures were inoculated into the medium with cholesterol and bile and isolate B11 has shown the highest cholesterol removal efficiency (88 ± 0.2%) with significant growth [Figure 3]. On similar notes, Liu et al [23] have studied cholesterol removal ability of Lactiplantibacillus plantarum Y15 through both in-vitro and in-vivo studies. They have observed high BSH activity in-vitro.…”
Section: Bacterial Growth and Cholesterol Removalmentioning
confidence: 98%
“…Metagenome analysis based on the V4 region of the 16S rRNA gene of gut microbiota showed that L. plantarum Y15 supplementation elevated the diversity of the microbial community and contrasted the increase in Proteobacteria (13.54%), increasing the relative abundances of Lactobacillus , Bifidobacterium , Bacteroides , Clostridium , Prevotella , and Oscillospira . The expression levels of gene encoding FXR and SHP, that increase the catabolism of cholesterol and biosynthesis of bile acids by the α-hydroxylase CYP7A1 in the liver, were reduced by L. plantarum Y15 supplementation, while CYP7A1 gene was significantly upregulated, thus indicating that L. plantarum Y15 supplementation could lower cholesterol by upregulating cholesterol degradation genes [ 45 ].…”
Section: Lactiplanibacillus Plantarummentioning
confidence: 99%